Noninvasive Evaluation of GIP Effects on β-Cell Mass Under High-Fat Diet - Kiyobayashi, Sakura; Murakami, Takaaki; Harada, Norio; Fujimoto, Hiroyuki; Murata, Yuki; Fujita, Naotaka; Hamamatsu, Keita; Ikeguchi-Ogura, Eri; Hatoko, Tomonobu; Lu, Xuejing; Yamane, Shunsuke; Inagaki, Nobuya (Frontiers in Endocrinology, 2022)
Pancreatic β-cell mass (BCM) has an importance in the pathophysiology of diabetes mellitus. Recently, glucagon-like peptide-1 receptor (GLP-1R)-targeted imaging has emerged as a promising tool for BCM evaluation. While glucose-dependent insulinotropic polypeptide/gastric inhibitory polypeptide (GIP) is known to be involved in high-fat diet (HFD)-induced obesity, the effect of GIP on BCM is still controversial. In this study, we investigated indium 111 (111In)-labeled exendin-4 derivative ([Lys12(111In-BnDTPA-Ahx)]exendin-4) single-photon emission computed tomography/computed tomography (SPECT/CT) as a tool for evaluation of longitudinal BCM changes in HFD-induced obese mice, at the same time we also investigated the effects of GIP on BCM in response to HFD using GIP-knockout (GIP-/-) mice. 111In-exendin-4 SPECT/CT was able to distinguish control-fat diet (CFD)-fed mice from HFD-fed mice and the pancreatic uptake values replicated the BCM measured by conventional histological methods. Furthermore, BCM expansions in HFD-fed mice were demonstrated by time-course changes of the pancreatic uptake values. Additionally, 111In-exendin-4 SPECT/CT demonstrated the distinct changes in BCM between HFD-fed GIP-/- (GIP-/-+HFD) and wild-type (WT+HFD) mice; the pancreatic uptake values of GIP-/-+HFD mice became significantly lower than those of WT+HFD mice. The different changes in the pancreatic uptake values between the two groups preceded those in fat accumulation and insulin resistance. Taken together with the finding of increased β-cell apoptosis in GIP-/-+HFD mice compared with WT+HFD mice, these data indicated that GIP has preferable effects on BCM under HFD. Therefore, 111In-exendin-4 SPECT/CT can be useful for evaluating increasing BCM and the role of GIP in BCM changes under HFD conditions.